Dam Engineering - Tosun, Hasan (IntechOpen, 2019)
Dams and their auxiliary structures are built to provide water for human consumption, irrigating lands, generating hydroelectric power, and use in industrial processes. They are critical structures for continuing life and providing public safety. Construction of a dam is a complicated task that requires sophisticated modern technology and technical expertise. Scientists need to review and adjust their perspectives on designing embankments and their related structures, and compaction and consolidation of fill material, behavior of concrete materials, geotechnical and seismological studies of the dam site, total risk analysis, safety monitoring and instrumentation, heightening, hydrological studies, soil conservation, and watershed management. This book intends to provide the reader with a comprehensive overview of the latest information in dam engineering.